Análise da influência da adição de poliestireno expandido (EPS) nas propriedades físico-mecânicas e comportamento térmico de argamassas cimentícias - Prata, Ana Larissa Cruz (2022)
With the advent of the NBR 15.575 standard, the requirements expected by the materials used in civil works became demanding in order to provide adequate habitability to its users. Allied to this, the current urgent need for the reuse/recycling of materials harmful to the environment can be the alternative to guarantee such habitability. In this scenario, expanded polystyrene (EPS), a polymer that presents poor waste management, can be applied in civil works in order to guarantee greater thermal comfort. To the detriment of this, the use in larger proportions can reduce the fundamental mechanical characteristics to guarantee a good performance during its use. Therefore, this work sought to analyze the physical-mechanical and thermal behavior characteristics of various EPS additions to replace sand, in order to compare them to the minimum requirements expected by the normative guidelines. At the end of the study, through the results obtained, it was possible to verify the valid percentages for the correct application in civil works.